Menyoal Kebohongan Publik konteks Aplikasi Maqashid Syari’ah Di Era 5.0 - Budiman, Ade (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
Recently now, that we were shocked by the news event both national and international levels, it’s about related to public lies that occur in Indonesian society, whether it's personal person’s, or comunal goup’s, or institutional institutions, it’s namely a policy justice that is blunt at the top and sharp at the bottom, and it’s as if giving a color to us of injustice that is evenly distributed among Indonesian society, especially among Muslims, it’s talks about the existence of a figure of person’s or group’s that has a strata rating at at the executive, judicial and legislative levels, which in this case violates the law when viewed from the existing facts and reality, so that in the context of Maqashid Syari'ah, This Study aims to discuss about public lies in the context of the Maqashid Syari'ah review it is necessary to review the potential for this public lies. with the sole intention of providing clear arguments and enlightenment regarding the existence of this phenomenon among Indonesian society. especially in the era 5.0 or society 5.0.